Restoration of the Posterior Glenoid in Recurrent Posterior Shoulder Instability Using an Arthroscopically Placed Iliac Crest Bone Graft: A Computed Tomography–Based Analysis - Camenzind, Roland S. (Orthop J Sports Med, 2021)
BACKGROUND: Posterior shoulder instability is uncommon, and its treatment is a challenging problem. An arthroscopically assisted technique for posterior iliac crest bone grafting (ICBG) has shown promising short- and long-term clinical results. Changes as shown on imaging scans after posterior ICBG for posterior shoulder instability have not been investigated in the recent literature. PURPOSE: To evaluate changes on computed tomography (CT) after arthroscopically assisted posterior ICBG and to assess clinical outcomes. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: Patients with preoperative CT scans and at least 2 postoperative CT scans with a minimum follow-up of 2 years were included in the evaluation. Of 49 initial patients, 17 (follow-up rate, 35%) met the inclusion criteria and were available for follow-up. We measured the glenoid version angle and the glenohumeral and scapulohumeral indices on the preoperative CT scans and compared them with measurements on the postoperative CT scans. Postoperatively, graft surface, resorption, and defect coverage were measured and compared with those at early follow-up (within 16 months) and final follow-up (mean ± SD, 6.6 ± 2.8 years). RESULTS: The mean preoperative glenoid version was –17° ± 13.5°, which was corrected to –9.9° ± 11.9° at final follow-up (P < .001). The humeral head was able to be recentered and reached normal values as indicated by the glenohumeral index (51.8% ± 6%; P = .042) and scapulohumeral index (59.6% ± 10.2%; P < .001) at final follow-up. Graft surface area decreased over the follow-up period, from 24% ± 9% of the glenoid surface at early follow-up to 17% ± 10% at final follow-up (P < .001). All clinical outcome scores had improved significantly. Progression of osteoarthritis was observed in 47% of the shoulders. CONCLUSION: Arthroscopically assisted posterior ICBG restored reliable parameters as shown on CT scans, especially glenoid version and the posterior subluxation indices. Graft resorption was common and could be observed in all shoulders. Patient-reported clinical outcome scores were improved. Osteoarthritis progression in almost 50% of patients is concerning for the long-term success of this procedure.